Effects of adding different proportions of soft rock on the dynamic change of the quality of aeolian sandy soil (Bangladesh Journal of Botany, 2021)
Evolution process of quality of soft rock and sand compound soil and exploration of its stability were studied. In the present study different proportions (1 : 1, 1 : 2, 1 : 5, 0 : 1) of soft rock and sand compound soil as the research object were selected. Tthe particulate organic carbon, microbial organic carbon, effective phosphorus, quick-acting potassium, nitro nitrogen and ammonium nitrogen in the compound soil were analyzed. Results showed that after 9 years of planting, the organic carbon content of particles with 0 : 1 treatment was the lowest, at 1.73 g/kg, and the treatment of 1 : 5 and 1 : 1 increased significantly by 74.74 and 94.90%, respectively. In the 20 - 30 cm soil layer, the lowest organic carbon content of particles with 1 : 2 treatment was 1.92 g/kg, and there was no significant difference between the other three treatments, with 0 : 1, 1 : 5 and 1 : 1 treatment increased by 46.20, 29.27 and 34.07%, respectively compared to 1 : 2 treatment. With developed root system, the biomass of the root system was greater than the biomass left on the ground after harvest, and the average content of organic carbon of the particles increased first and then decreased later. The microbial community in the compound soil was significantly improved, and the carbon content of microorganisms in the treatment of 1 : 1, 1 : 2 and 1 : 5 was significantly higher than that of whole sand by 85, 165 and 143%, respectively, after multi-year of cultivation. The soil root microbial community showed a benign development. With the increase of planting years, the incorporation of soft rock accelerates the process of natural succession of soil quality. Compared with sandy land, compound soil has significantly improved storage of available phosphorus and available potassium nutrients. Compound soil has been cultivated for 9 years compared with 6 years, with the ratio of 1 : 1, 1 : 2, 1 : 5 and 0 : 1, the effective phosphorus content increased significantly by 141, 181, 169 and 63% respectively, the available potassium content increased significantly by 141, 181, 169 and 63% respectively. Compound soil has been cultivated for 9 years compared with 6 years, with the ratio of 1 : 1, 1 : 2, 1 : 5, and 0 : 1, the nitrate nitrogen content increased significantly by 40, 130, 135 and 120%, respectively. Nitro nitrogen is easily soluble in water, and the higher the proportion of sand in the compound soil, the easier the loss of nitrous nitrogen content in the soil. After multiple years of cultivation, the ammonium nitrogen content in the compound soil decreased, with a significant decrease of 35 (p < 0.05), 34 (p < 0.05), 45 (p < 0.05) and 37% (p < 0.05), respectively. Due to the disruption of harvest, the exposure of the surface soil is high, which causes ammonium nitrogen to evaporate.Bangladesh J. Bot. 50(3): 837-845, 2021 (September) Special